The Effectiveness of Audit Committees and its Impact on Earnings Management: Empirical Evidence in UK Public Companies - ZHANG, HAN (2016)
This research investigates whether size, frequency of activities and independence of UK public firms’ audit committees have effects on the quality of earnings. Thus, this study contributes to the empirical literatures of audit committee effectiveness and earnings management in UK market that are different from the US environment in terms of accounting and corporate governance. In particular, an in-depth analysis is conducted by observing the relationship between audit committee characteristics and extreme high or low estimated abnormal accruals in order to investigate how audit committees effectively constrain earnings management. Using different abnormal accruals measures, one with positive and one with negative abnormal accruals, I observe significant relation between audit committee characteristics and earnings management. A significant positive association is found between audit committee size and income-increasing earnings management. It is unable to confirm whether the audit committee activity level, which is measured by the frequency of meetings has impact on earnings quality since insignificant relation is found. I also provide evidence on audit committee with solely independent directors are more effectively in constraining both income-increasing and income-decreasing earnings management. Additionally, a minimum level of independence is suggested which is related to lower likelihood of upward earnings management.